PENGARUH FAKTOR SUHU DAN KELEMBABAN TERHADAP PEMBUNGAAN DAN PEMBUAHAN TANAMAN BUAH NAGA (Hylocereus polyrhizus) - Yeni Eka Lestari; Kanthi Pangestuning; Ahmad Hadi (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2024)
The influence of temperature and humidity on the flowering and fruiting of dragon fruit plants is crucial to understand. This research was conducted from October 2023 to February 2024 in the paddy fields of Ringin Putih Village, Muncar District, Banyuwangi Regency. The method used in this study was quantitative analysis method with multiple linier rwgression statistical calculations. The type of data used is real-time data (temperature, humidity, and observation parameters) for 5 months in the field. The parameters observed were the number of emerging flowers, the number of blooming flowers, the final fruit count, fruit weight, and fruit sweetness level. The result of this study indicate that temperature and humidity do not affect flowering in terms of the number of emerging flowers, but they do affect the number of blooming flowers. As for fertilization, there is no effect on the final fruit count, fruit weight, and fruit sweetness.